Protection for HVDC Transmission Lines Based on Current Ratio of DC Filter and Smoothing Reactor - Ningning Liu; Yongli Li; Tao Li; Song Li; Jinghan He; Xinzhou Dong (CSEE Journal of Power and Energy Systems)
A new line protection for HVDC systems using the ratio of currents of a DC filter and smoothing reactor is presented. Characteristic analysis on a DC filter shows that it behaves like an inductor at a high frequency band whose inductance is far less than the sum of smoothing reactor inductance plus converter equivalent inductance. Based on this characteristic, fault analysis shows that during high-frequency DC line faults (on either side), the DC filter current amplitude significantly exceeds that of the smoothing reactor, with a current ratio much greater than 1. Whereas for external faults, near faulty end, DC filter current amplitude is less than the one of a smoothing reactor and current ratio at this end is smaller than 1, while the current ratio at the distance faulty end is still far greater than 1. The effectiveness of the protection is verified by a large number of simulation experiments. It does not need synchronization of signals at both ends. In addition, it has high sensitivity for high-resistance faults, and is insensitive to the length of DC transmission line and power flow change.